Thermal control component including wet gel felt
By using wet gel felt with high moisture content as a thermal control component in the battery module and battery pack, the problems of flame spread and explosion are solved, effective heat absorption and fire extinguishing functions are achieved, and thermal insulation performance and economic feasibility are improved.
Patent Information
- Application Number
- CN202480004071.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-18
- Filing Date
- 2024-04-17
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to effectively prevent flame spread and explosion in battery modules and battery packs, and traditional thermal insulation materials are difficult to meet the dual requirements of heat insulation and fire protection when the battery is thermally out of control.
A wet gel felt with a moisture content of 50 wt% or more is used as a heat control component. The high content of the wet gel felt and the specific pore structure are used to achieve heat absorption and fire extinguishing functions, and the wet gel felt is sealed in the shell to improve thermal insulation performance.
Effectively suppressing the spread of fires and preventing explosions, improving the safety of battery modules and battery packs, while improving economic feasibility due to process simplification and cost reduction.
Smart Images

Figure CN119894825A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0050758 filed on April 18, 2023, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field
[0003] The present invention relates to a thermal control component including a wet gel felt and a battery including the thermal control component. Background Art
[0004] In order to reliably control heat in hot areas from small spaces and to provide product safety and prevent the spread of fire, appropriate thermal insulation is required in the fields of electronics, industry and automotive technology. Thermal insulation sheets with excellent properties when compressed can be used as separators in lithium-ion battery modules, for example.
[0005] More specifically, various thermal insulation materials including aerogels are being used to prevent fires caused by thermal runaway of batteries, which occur in electric vehicles, electric boats, etc. However, it is difficult to fundamentally prevent the occurrence of fires by thermal insulation alone. In particular, since the space in which thermal control components can be applied inside the battery is limited, it is difficult to ensure the insulation thickness required to block the fire source, so that the spread of the fire can only be delayed as much as possible.
[0006] Electronic products such as laptops, OLEDs, or TVs have hot spots caused by heat sources, which may reduce the emotional quality perceived by consumers due to partial heat dissipation from the surface of the device. In addition, if the heat is not properly diffused to the outside due to the use of simple thermal insulation materials, the excessive accumulation of heat may cause system failure, shorten the life of the product, or even cause an explosion or fire. In order to solve the problems caused by this heat generation, various thermal insulation materials have been applied, but so far, the best thermal insulation material that is thin and has excellent thermal insulation performance has not been developed, so various research and technology development on thermal insulation are being carried out.
[0007] In order to solve the above typical problems, there is a case where aerogel is applied, and aerogel is attracting attention as a highly efficient thermal insulation material. Aerogel is a highly porous material composed of nanoparticles, and has high porosity, large specific surface area, and low thermal conductivity, so it is attracting attention as a highly efficient thermal insulation material, sound insulation material, etc.
[0008] At the same time, this aerogel has very low mechanical strength due to its porous structure, and an aerogel composite is prepared and used by impregnating and combining fibers such as inorganic fibers or organic fibers (which are typical insulating fibers) with aerogel, and the aerogel composite has weak adhesion between the fibers and the aerogel, so that the aerogel particles are separated during processing such as cutting and bending, thereby generating dust and reducing durability, which may cause damage to the device, etc. when the aerogel composite is used as an insulating material for electronic products.
[0009] Therefore, it is highly desirable to develop a material that can prevent flames from ignition and explosion of battery modules and battery packs from spreading to adjacent battery modules regardless of the capacity of the battery and the increase in size of the battery modules and battery packs. Summary of the invention
[0010] Technical issues
[0011] An object of the present invention is to provide a heat control member capable of effectively achieving heat insulation and fire occurrence suppression performance by including a wet gel felt having a water content of 50 wt % or more.
[0012] Technical Solution
[0013] In order to achieve the above-mentioned object, the present invention provides a heat control component, a battery having the heat control component, and a method for manufacturing the heat control component.
[0014] (1) The present invention provides a heat control component including a wet gel felt and a housing accommodating the wet gel felt therein, the wet gel felt having a water content of 50 wt % or more according to the following equation 1.
[0015] [Equation 1]
[0016] Water content (%) = [(ab) / a] × 100
[0017] In the above Formula 1, a is the weight of the wet gel felt before drying, and b is the weight of the wet gel felt after drying in a convection oven at 150° C. for 24 hours.
[0018] (2) In the above (1), the present invention provides a heat control component, wherein the moisture content of the wet gel felt is 60% to 90%.
[0019] (3) In the above (1) or (2), the present invention provides a thermal control component, wherein when the wet gel felt is dried in a convection oven at 150°C for 24 hours, the average pore size of the wet gel is 1 nm to 50 nm.
[0020] (4) In any one of the above (1) to (3), the present invention provides a thermal control component, wherein the thermal conductivity of the wet gel is 30 mW / mK to 70 mW / mK after the wet gel felt is dried in a convection oven at 150°C for 24 hours.
[0021] (5) In any one of the above (1) to (4), the present invention provides a heat control component, wherein the wet gel felt is a silica wet gel felt.
[0022] (6) In any one of the above (1) to (5), the present invention provides a thermal control component, wherein the wet gel felt comprises a wet gel and a felt substrate, wherein the felt substrate is one or more selected from a film, a sheet, a net, a fiber, a porous body, a foam body and a non-woven fabric body.
[0023] (7) In any one of the above (1) to (6), the present invention provides a heat control component, wherein the housing is a bag.
[0024] (8) In the above (7), the present invention provides a heat control component, wherein the bag is made of polyethylene (PE), polyester (PET), polypropylene (PP), aluminum or a composite material thereof.
[0025] (9) The present invention provides a battery comprising the heat control member according to any one of (1) to (8) above.
[0026] (10) The present invention provides a method for preparing a thermal control element, wherein the preparation method comprises: 1) preparing a silica sol; 2) preparing a shell that accommodates a felt substrate therein; 3) injecting the silica sol into the shell to impregnate the felt substrate with the silica sol, and then sealing the shell; and 4) gelling the silica sol impregnated into the felt substrate to form a silica wet gel felt.
[0027] Beneficial Effects
[0028] The wet gel felt contained in the heat control component according to the present invention has a high content of internal moisture, thereby exhibiting excellent heat absorption and fire extinguishing effects, so that the wet gel felt can be used in articles to effectively prevent the occurrence of fire and the spread of fire. In addition, compared with the aerogel felt that has been used as a typical thermal insulation material, the production process is shortened and the production cost is reduced, thereby also improving economic feasibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a graph showing the pore distribution of the wet gel mats of Examples 2 to 4 after drying; and
[0030] Figure 2It is a schematic diagram showing the evaluation method of the flame blocking performance. DETAILED DESCRIPTION
[0031] Hereinafter, the present invention will be described in more detail to facilitate understanding of the present invention.
[0032] It should be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in commonly used dictionaries. It will be further understood that, based on the principle that the inventor can appropriately define the meaning of words or terms to best explain the present invention, words or terms should be interpreted as having a meaning consistent with their meanings in the context of the relevant field and the technical concept of the present invention.
[0033] Hereinafter, the present invention will be described in detail.
[0034] The heat control component of the present invention is characterized by including a wet gel felt having a water content of 50 wt % or more according to the following Equation 1 and a housing accommodating the wet gel felt therein.
[0035] [Equation 1]
[0036] Water content (%) = [(ab) / a] × 100
[0037] In the above formula 1, a is the weight of the wet gel felt before drying, and b is the weight of the wet gel felt after drying at 150° C. in a convection oven for 24 hours.
[0038] In the present invention, "wet gel" refers to a product having a network structure produced by the gelation reaction of the sol, and refers to a gel containing a solvent in a state before drying. The wet gel contains a large amount of water inside it, so when exposed to high temperatures such as thermal runaway of a battery, an endothermic reaction occurs as the water evaporates, and an effect occurs that does not increase the temperature of the opposite side until all the water evaporates. In addition, when all the water evaporates, thereby completing the drying, the wet gel can be used as a felt-type thermal insulation material based on silica gel having nanopores.
[0039] In the wet gel felt included in the thermal control component of the present invention, the wet gel exists in a state of being contained and sealed in a shell while containing moisture in its pores, and therefore, does not generally act as a thermal insulating material, but plays a role in controlling heat when the internal moisture evaporates in the event of a problem such as thermal runaway.
[0040] In the present invention, the moisture content according to the above equation 1 is the content of moisture contained inside the wet gel felt, which represents the weight ratio of moisture in the total weight including the wet gel and the felt. This can be calculated by comparing the weight of the wet gel felt before drying and the weight reduction after drying in a convection oven at 150° C. for 24 hours, from the amount of evaporated moisture obtained by equation 1.
[0041] In the present invention, the water content according to the above Formula 1 is 50 wt % or more, and more specifically, may be 50 wt % or more, 60% to 90%, 60% or more, 65% or more, 90% or less, or 85% or less.
[0042] In the present invention, the average pore size of the wet gel may be 1 nm to 50 nm, specifically 5 nm to 50 nm, more specifically 10 nm to 40 nm. The average pore size may be measured after drying the wet gel felt at 150° C. in a convection oven for 24 hours.
[0043] As described above, the wet gel used in the present invention has the property of having a small average pore size, and thus can exhibit excellent thermal insulation performance.
[0044] In the present invention, the thermal conductivity of the wet gel felt may be 30 to 70 mW / mK, specifically 40 to 60 mW / mK. The thermal conductivity may be measured after drying the wet gel felt at 150° C. in a convection oven for 24 hours.
[0045] Through the above characteristics, the heat control component of the present invention can suppress the spread of fire through the heat absorption function in the early stage of fire, and thereafter, can be used as a heat insulating material to effectively prevent heat transfer to the surrounding area.
[0046] In the present invention, the wet gel felt includes a wet gel and a felt substrate, and the felt substrate according to one embodiment of the present invention may specifically be a porous substrate. If a porous felt substrate is used, the silica sol easily penetrates into the substrate, and thus, a wet gel is uniformly formed inside the felt substrate, so that the prepared wet gel felt may have excellent thermal insulation.
[0047] The felt substrate that can be used according to one embodiment of the present invention can be a film, a sheet, a net, a fiber, a porous body, a foam, a nonwoven fabric body or a laminate of two or more layers thereof. In addition, depending on its use, the felt substrate can have a surface roughness formed or patterned on its surface. More specifically, the felt substrate can be a fiber that can further improve thermal insulation performance by including a space or a gap, and a wet gel can be easily inserted into the felt substrate through the space or the gap. In addition, the felt substrate can preferably have a low thermal conductivity.
[0048] Specifically, the felt substrate can be polyamide, polybenzimidazole, polyaramid, acrylic resin, phenolic resin, polyester, polyetheretherketone (PEEK), polyolefin (for example, polyethylene, polypropylene, their copolymers, etc.), cellulose, carbon, cotton, wool, linen, non-woven fabrics, glass fiber, ceramic wool or ceramic paper, etc. More specifically, the felt substrate in the present invention can be ceramic paper.
[0049] In the present invention, the housing contains the wet gel felt, and the form of sealing the wet gel felt is not limited. In addition, the housing can have a bag shape, a square or a cylindrical shape, etc., but is not limited thereto, and any housing that can contain the wet gel felt and is properly sealed and contained in the thermal control component can be applied.
[0050] The material of the bag is not particularly limited, and a material that can effectively block moisture, such as polyethylene (PE), polyester (PET), polypropylene (PP), aluminum, or a composite material thereof, may be used.
[0051] Furthermore, the thermal control components of the present invention may be included and used in batteries.
[0052] The thermal control component of the present invention contains a large amount of water, so an endothermic reaction can be performed through the evaporation of water, so that in the event of thermal runaway of the battery cell, heat will not be transferred to adjacent cells, and the cell experiencing thermal runaway can be effectively cooled, thereby extinguishing the fire.
[0053] In addition, after all the internal moisture evaporates, the heat control component acts as a heat insulation component to effectively prevent uncooled heat from being transferred from the battery cell that has thermal runaway to adjacent batteries. As a result, chain thermal runaway and fire of battery cells in electric vehicles can be prevented.
[0054] Specifically, the thermal control component of the present invention can be arranged on the outside of the bus bar for electrically connecting the electrode tabs, or can be applied to at least a portion of the interior of the battery pack housing, thereby preventing more oxygen than the minimum amount of oxygen for combustion from flowing into the battery modules and battery packs where fire and flames occur, and preventing the heat and flames inside the battery modules and battery packs from spreading to the outside.
[0055] Specifically, in the event of a fire in a battery module, the thermal control component of the present invention first effectively cools the battery by absorbing heat, and thereafter acts as a high-performance thermal insulation material with micropores, thereby simultaneously performing the functions of preventing the spread of fire and subsequent processing.
[0056] In addition, the wet gel felt of the present invention may be a silica wet gel felt, and, for example, the heat control component of the present invention may be produced by the following method.
[0057] Specifically, the thermal control component of the present invention can be manufactured by a method including the following steps: 1) preparing a silica sol; 2) preparing a shell that accommodates a felt substrate therein; 3) injecting the silica sol into the shell to impregnate the felt substrate with the silica sol, and then sealing the shell; and 4) gelling the silica sol impregnated into the felt substrate to form a silica wet gel felt.
[0058] Step 1)
[0059] Step 1 is a step of preparing a silica sol, which can be prepared by mixing a silica precursor and a gelling catalyst, and water may be added thereto as necessary.
[0060] The silica precursor may specifically be a water glass solution, and in the silica sol, the gelling catalyst may be introduced in an amount of 2.8 wt % to 17 wt % relative to the water glass in the water glass solution.
[0061] The water glass solution may be a diluted solution in which distilled water is added to water glass and then mixed therewith, and the water glass may be sodium silicate, potassium silicate or lithium silicate, which is an alkaline silicate (Na2SiO3) obtained by melting silicon dioxide (SiO2) and an alkali.
[0062] The water glass dispersion may contain 3 wt % to 30 wt % of silicon dioxide (SiO 2). If silicon dioxide is contained in the water glass dispersion at a content lower than the above range, a gel structure may not be properly formed, and if silicon dioxide is contained in the water glass dispersion at a content higher than the above range, silicon dioxide may be precipitated together when a catalyst is introduced, and a gel having uneven pores may be formed, thereby reducing the pore size and specific surface area.
[0063] The gelling catalyst is not particularly limited, and any one or more of organic acids, inorganic acids and carbonates can be used, for example, one or more selected from acetic acid, oxalic acid, nitric acid, hydrochloric acid, sulfuric acid, hydrofluoric acid and ethylene carbonate can be used. Specifically, the gelling catalyst can be ethylene carbonate.
[0064] The content of the acid catalyst may make the pH of the silica sol 4 to 8. If the pH of the silica sol is outside the above range, gelation in step 3) described later may not be easily achieved, or the gelation rate may be too low, so that processability may be reduced.
[0065] Step 2)
[0066] Step 2) is a step of preparing a housing that accommodates the felt base material therein.
[0067] When the felt substrate is housed in a shell, for example, when the shell is a bag, the felt substrate can be introduced from one side of the bag sealed on the other three sides, or a bag with one open edge can be made by arranging films on the upper and lower sides of the felt substrate and bonding the films on the outer sides of the three sides of the felt substrate to each other.
[0068] Step 3)
[0069] The above step 3) is a step of injecting silica sol into the housing to impregnate the felt base material with the silica sol, and then sealing the housing.
[0070] After all the silica sol is injected into the shell, the opening surface of the shell can be sealed to seal the shell. At this time, in order to fully remove the air inside the shell, the sealing process can be performed under a low vacuum state of 1Torr to 760Torr. In order to promote the bonding between the felt substrate and the silica sol in the sealed shell, the felt substrate can be gently pressed to fully impregnate. Afterwards, in step 4) described later, the felt substrate can be pressed to a predetermined thickness under a constant pressure to prepare a silica wet gel felt with a uniform thickness.
[0071] Step 4)
[0072] The above step 4) is a step of gelling the silica sol impregnated into the felt base material to form a silica wet gel felt.
[0073] Here, gelation may be a sol-gel reaction, and the "sol-gel reaction" may be the formation of a network structure from a silicon unit precursor material.
[0074] Here, the network structure may be a planar mesh structure in which specific polygons having one or more types of atomic arrangements are connected to each other, or a structure in which specific polyhedrons share their vertices, edges, faces, etc. with each other to form a three-dimensional skeleton structure.
[0075] The preparation method according to one embodiment of the present invention may further include a step of aging the prepared silica wet gel felt after the gelation in the above step 4).
[0076] The aging is not particularly limited, but, for example, can be performed by leaving the prepared silica wet gel felt to stand at a temperature of 50° C. to 90° C. for 1 hour to 24 hours.
[0077] According to the preparation method of one embodiment of the present invention, aging is performed after the silica wet gel felt is prepared, so that the network structure of the wet gel in the silica wet gel felt can be further firmly formed, and thus the pore performance can be excellent.
[0078] Example
[0079] Hereinafter, the present invention will be described in more detail with reference to Examples. However, the following Examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0080] Example 1
[0081] 12 parts by weight of water glass and 75 parts by weight of water are mixed to prepare silica sol. After this, 2 parts by weight of acetic acid are introduced into the silica sol as a gelling catalyst to prepare a catalytic sol. 3 mm thick ceramic paper is put into a PE / aluminum / PP bag with three sealed edges as a felt substrate, and then the catalytic sol is injected into the bag to be impregnated into the felt substrate, and a vacuum sealer is used to reduce pressure on one opening edge of the bag and apply heat to seal. The silica sol impregnated into the felt substrate in the sealed bag is gelled to prepare a wet gel felt.
[0082] Examples 2 to 6
[0083] A wet gel mat was prepared in the same manner as in Example 1, except that changes were made as shown in Table 1 below.
[0084] Example 7
[0085] 21 parts by weight of water glass and 67 parts by weight of water are mixed to prepare silica sol. After this, 5 parts by weight of acetic acid are introduced into the silica sol as a gelling catalyst to prepare a catalytic sol. 2 mm thick ceramic paper is put into a PE / aluminum / PP bag with three sealed edges as a felt substrate, and then the catalytic sol is injected into the bag to be impregnated into the felt substrate, and a vacuum sealer is used to reduce pressure on one opening edge of the bag and apply heat to seal. The silica sol impregnated into the felt substrate in the sealed bag is gelled to prepare a wet gel felt.
[0086] Example 8
[0087] 21 parts by weight of water glass and 67 parts by weight of water are mixed to prepare silica sol. Thereafter, 5 parts by weight of acetic acid are introduced into the silica sol as a gelling catalyst to prepare a catalytic sol. A 3 mm thick organic fiber is placed in a PE / aluminum / PP bag with three sealed edges as a felt substrate, and then the catalytic sol is injected into the bag to be impregnated into the felt substrate, and a vacuum sealer is used to reduce pressure on one opening edge of the bag and apply heat to seal. The silica sol impregnated into the felt substrate in the sealed bag is gelled to prepare a wet gel felt.
[0088] Example 9
[0089] 20 weight parts of water glass and 64 weight parts of water are mixed to prepare silica sol. After this, 5 weight parts of acetic acid are introduced into silica sol as gelling catalyst to prepare catalytic sol. PET film is respectively arranged on the upper surface and lower surface of ceramic paper with a thickness of 3mm, and the PET film of the upper surface and lower surface is bonded by acrylic adhesive along the outside of the three edges of ceramic paper, thereby sealing three edges. Then catalytic sol is injected into a bag through an open edge to be impregnated into felt substrate, and the PET film on an open edge is bonded and sealed using acrylic adhesive. The silica sol gelled to be impregnated into the felt substrate in a sealed bag to prepare wet gel felt.
[0090] [Table 1]
[0091]
[0092] Comparative Example 1
[0093] 28 parts by weight of water glass and 54 parts by weight of water were mixed to prepare a silica sol. Thereafter, 7 parts by weight of acetic acid was introduced into the silica sol as a gelling catalyst to prepare a catalytic sol. A 3 mm thick ceramic paper was placed in a mold, impregnated with the catalytic sol, and then gelled to prepare a wet gel felt.
[0094] The prepared wet gel felt was dried in a convection oven at 150°C for 24 hours to remove as much moisture as possible from the inside of the gel, thereby obtaining a dried felt. The dried felt was introduced into a PE / aluminum / PP bag with three sealed edges, and one open edge thereof was decompressed and heated to seal using a vacuum sealer.
[0095] Comparative Example 2
[0096] Tetraethyl orthosilicate (TEOS) and water are mixed in a molar ratio of 1:4, and ethanol is added thereto in a weight ratio of 1:1 relative to TEOS to prepare a silica precursor solution. In order to promote hydrolysis, hydrochloric acid is added so that the pH of the silica precursor solution is 3 or less, and stirred for 2 hours or more to prepare a hydrated TEOS solution. Ethanol having a weight ratio of 1:4 relative to the hydrated TEOS solution is added to prepare a silica sol. In order to improve thermal insulation and flame retardant properties, 0.2 parts by weight of a sunscreen and a flame retardant are added based on 100 parts by weight of the silica sol.
[0097] An alkaline catalyst solution (5 wt% NaOH aqueous solution) was added so that the volume ratio of the catalytic sol to the alkaline catalyst solution was 99:1 to prepare a catalytic sol. The catalyzed sol was impregnated into a substrate for felt and gelled. Thereafter, aging and surface modification were performed in a 10 wt% TMES solution at 60°C for 16 hours. The prepared wet gel felt was placed in a supercritical extractor, and CO2 was then injected into it, after which the temperature inside the extractor was raised to 60°C over the course of 1 hour, and then supercritical drying was performed at 60°C and 100 bar to prepare a hydrophobic aerogel felt.
[0098] Comparative Example 3
[0099] 0.6 parts by weight of starch was added to 77.4 parts by weight of water and dispersed to prepare an aqueous solution, which was then absorbed into 22 parts by weight of a super absorbent polymer (SAP) to prepare a hydrogel.
[0100] The prepared hydrogel was introduced into a PE / aluminum / PP bag with three sealed edges, and one open edge thereof was decompressed and heat was applied to seal it using a vacuum sealer. The final thickness of the sealed bag was 3 mm.
[0101] Experimental Example 1: Water content (wt%)
[0102] The weight of the wet gel felt was measured (a), and then the wet gel felt was dried in a convection oven at 150° C. for 24 hours to measure the weight after drying (b). The moisture content of the wet gel felt was measured according to Equation 1 below.
[0103] [Equation 1]
[0104] Water content (%) = [(ab) / a] × 100
[0105] Experimental Example 2: Time (seconds) required to reach 100°C backside temperature compared to 1000°C torch
[0106] A sample with a size of 20 cm x 20 cm was prepared and mounted vertically on a stand. Temperature sensors were placed at the center of the front and rear surfaces of the mounted sample.
[0107] The flame of a torch using butane gas was sprayed onto the position of the temperature sensor on the front surface of the sample, and then the distance between the sample and the torch was adjusted so that the temperature of the front surface was 1000° C. The time required for the temperature of the back surface of the sample to reach 100° C. was recorded by the temperature sensor on the back surface of the sample.
[0108] [Table 2]
[0109]
[0110] As shown in Table 2 above, when the high-temperature torch flame is sprayed onto the sample, the wet gel felt containing excessive moisture inside the gel undergoes an endothermic effect until all the moisture evaporates, thereby preventing the temperature on the back surface from exceeding 100 °C, and making the time taken for the back surface temperature to reach 100 °C significantly delayed compared to the dry gel without moisture. In addition, in the part directly in contact with the torch flame, the moisture quickly dries, making this part function as a thermal insulation material with nanopores, thus exhibiting excellent thermal insulation performance. As a result, the time required for the back surface temperature to reach 100 °C is further delayed.
[0111] Since Comparative Examples 1 and 2 do not contain moisture in the gel, the temperature on the back surface rises very quickly compared to the Examples. Comparative Example 2 prepares an aerogel felt. Therefore, it has better thermal insulation performance than Comparative Example 1, which results in a delayed increase in the back surface temperature, but does not play an endothermic role, making the back surface temperature reach 100 °C faster than in the Examples.
[0112] Different from the Examples of this specification using silica sol, Comparative Example 3 is a case of using a hydrogel. And although the water content in its gel is as high as that in the Examples, different from the Examples, there is no felt substrate in Comparative Example 3, and no hard gel structure is formed. Therefore, it has been confirmed that during the 1000 °C torch test, the seal of the bag ruptured due to the pressure caused by boiling moisture, and the gel was ejected to the outside. As a result, a large amount of gel was lost, making Comparative Example 3 exhibit significantly lower adiabatic performance than the Examples. And when Comparative Example 3 is continuously heated, it has been confirmed that since no adiabatic structure remains inside after all the moisture has evaporated, the temperature of the back surface tends to rise at a very fast rate.
[0113] Experimental Example 3: Pore Distribution Observation
[0114] The wet gel felt was dried in a convection oven at 150 °C for 24 hours to obtain a sample with all moisture removed. 0.1 g of the dried sample was placed in a BET special glass cup, connected to a pretreatment device, and then pretreated at 150 °C for 12 hours while reducing the pressure to a pressure of 1 Torr to 760 Torr to remove impurities in the sample, including moisture. Using a 3FLEX device of Micrometrics Co., the pore distribution of the pretreated sample was analyzed by the adsorption / desorption amount of nitrogen according to the partial pressure (0.11 < p / p0 < 1).
[0115] As Figure 1As shown, it can be seen that the wet gel felts corresponding to Examples 2 to 4 each exhibited a very uniform and narrow pore distribution after drying, thereby confirming that the wet gel felt has excellent thermal insulation performance. In particular, since most of the pores are in the range of 10nm to 50nm, which is a mesoporous region, the thermal insulation performance is even more excellent, but it has been confirmed that the wet gel felts can each be used as an excellent thermal insulation material even after the moisture has dried due to exposure to high temperatures.
Claims
1. A thermal control component, comprising: A wet gel felt having a water content of 50 wt % or more according to the following equation 1; and a housing containing the wet gel felt therein; [Equation 1] Water content (%) = [(ab) / a] × 100 Where in the above equation 1, a is the weight of the wet gel felt before drying, and b is the weight of the wet gel felt after drying in a convection oven at 150°C for 24 hours.
2. The thermal control component according to claim 1, wherein the wet gel felt has a water content of 60% to 90%.
3. The thermal control component of claim 1, wherein the average pore size of the wet gel is 1 nm to 50 nm after the wet gel felt is dried in a convection oven at 150°C for 24 hours.
4. The thermal control component of claim 1, wherein the thermal conductivity of the wet gel is 30 mW / mK to 70 mW / mK after the wet gel felt is dried in a convection oven at 150°C for 24 hours.
5. The thermal control component of claim 1, wherein the wet gel felt is a silica wet gel felt.
6. The thermal control component according to claim 1, wherein the wet gel felt comprises a wet gel and a felt substrate, wherein the felt substrate is one or more selected from the group consisting of a film, a sheet, a net, a fiber, a porous body, a foam body, and a nonwoven fabric body.
7. The thermal control component according to claim 1, wherein: The housing is a bag.
8. The thermal control component according to claim 7, wherein: The bag is made of polyethylene (PE), polyester (PET), polypropylene (PP), aluminum or a composite material thereof. 9 . A battery comprising the heat control component according to claim 1 .
10. A method of producing a thermal control component, the method comprising: 1) preparing silica sol; 2) preparing a housing that contains a felt substrate; 3) injecting the silica sol into the housing to impregnate the felt substrate with the silica sol, and then sealing the housing; and 4) The silica sol impregnated into the felt substrate is gelled to form a silica wet gel felt.
Citation Information
Patent Citations
Pedal Shoe Spatula
KR1020230050758A